(untitled) (Reflection and Critique Law Magazine, 2022)
We are experiencing an information society, where more than four billion people on the planet have access to the internet, feeding the web and producing data. Working with the large mass of data is not an easy task for that the organizations can transform it into useful information for the decision-making process. Some tools have been standing out in this area, with the objective of transforming data into information, being them the algorithms and artificial intelligence. The use of technologies by organizations to obtainment of a competitive advantage is currently concentrated on the web, creating new markets, which go beyond the borders of nations, and assets, that governments do not control and have difficulties in monitoring, such as cryptocurrencies. These new markets present planetary characteristics and the institutional framework needs to guarantee the rights of the agents involved in these markets. In this context, through the deductive reasoning method and bibliographic and documentary research techniques, this study aimed to discuss the following questions: to what extent do legal science and technology interact in the information society? What is the new role of legal norms on technological dynamics that influence interactions between markets and individuals? Among the contributions of this study, we highlight the historical record of the evolution of social relations on the web, and its impacts on the markets, as well as the performance of legal rules in guaranteeing the legitimacy of these transactions.